Surgical site infections: A one year prospective study in a tertiary care center - Shahane, Varsha Dattatraya; Bhawal, Saikat; Lele, Upendra (International Journal of Health Sciences, 2012)
Background: Surgical Site Infections (SSI) is the third most commonly reported nosocomial infection which has an adverse impact on the hospital as well as on the patient. A continuous surveillance is called for, to keep a check on the occurrence of SSI. Objectives: a) to study the incidence of SSI in our hospital. b) to study the risk factors of SSI in our hospital. c) to identify the areas in our hospital, which need to be strengthened and dealt with proactive measures to curb the incidence of SSI, which is an indicator of health care system in a given set up. Methodology: We conducted a one year study of SSI in our hospital. 300 cases of Surgery and Obstetrics and Gynaecology were included in the study. A few host factors, wound factors and surgery related factors that cause SSI were studied. Swabs were collected from the infected surgical wounds and processed by the conventional microbiological methods. Antimicrobial susceptibility was done by Kirby-Bauer disc diffusion method. Results: Prolonged surgery (>2hours) and insertion of drain were found to be significantly associated with occurrence of SSI and the clean surgeries showed minimum risk of infection. Escherichia coli (31.25%) was the commonest pathogen, followed by Pseudomonas aeruginosa (25 %) and Staphylococcus aureus 22% .The incidence of SSI in our set up is 6%. Conclusions: The outcome of the SSI surveillance in our hospital revealed that in order to decrease the incidence of SSI we would have to: a) decrease the duration of the surgeries performed b) focus on regular and intensive drain care c) identify poor risk patients and ensure their proper management d) conduct periodic surveillance to keep a check on SSI. Key words: SSI, incidence, risk factors, clean surgery, pathogen